Demographic shifts in eastern US forests increase the impact of late‐season drought on forest growth. Issue 10 (14th July 2020) - Au, Tsun Fung; Maxwell, Justin T.; Novick, Kimberly A.; Robeson, Scott M.; Warner, Scott M.; Lockwood, Benjamin R.; Phillips, Richard P.; Harley, Grant L.; Telewski, Frank W.; Therrell, Matthew D.; Pederson, Neil
Abstract : While forest communities are changing as a result of global environmental change, the impacts of tree species shifts on ecosystem services such as carbon storage are poorly quantified. In many parts of the eastern United States (US), more xeric‐adapted oak‐hickory dominated stands are being replaced with mesic beech‐maple assemblages. To examine the possible impacts of this ongoing change in forest composition, we investigated how two wide‐ranging and co‐occurring eastern US species – Acer saccharum (sugar maple) and Quercus alba (white oak) – respond to interannual climate variability. Using 781 tree cores from 418 individual trees at 18 locations, we found late‐growing season drought reduced A. saccharum growth more than that of Q. alba . A gradient in the growth reduction across latitude was also found in A. saccharum, where southern populations of A. saccharum experienced greater reductions in growth during drought. Drought had a legacy effect on growth for both species, with drought occurring later in the growing season having a larger legacy effect. Consequently, as forests shift from oak to maple dominance, drought in the later part of the growing season is likely to become an increasingly important control on forest productivity. Thus, our findings suggest that co‐occurring species are responding to environmental conditions during different times in the growing season and, therefore, the timing of drought conditions will play an important role in forest productivity and carbon sequestration as forest species composition changes. These findings are particularly important because the projected increases in potential evapotranspiration, combined with possible changes in the seasonality of precipitation could have a substantial impact on how tree growth responds to future climatic change.